Prevalence and Genetic Diversity of Aichi Viruses in Wastewater and River Water in Japan - Kitajima, Masaaki (American Society for Microbiology (ASM), 2011)
Aichi virus (AiV) genomes were detected in 12 (100%) influent and 11 (92%) effluent wastewater and 36 (60%) river water samples. Among 260 strains identified, 255 were genotype A and 5 were genotype B. This is the first report describing the molecular characterization of AiVs in aquatic environments in Japan.